ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN E-WALLET (OVO) PADA MASYARAKAT DI KOTA MALANG - Widi, Krisna Darma; Girindra Mega Paksi (Journal of Development Economic and Social Studies, 2024)
This research was conducted to determine the factors that influence the OVO E Wallet in the community in Malang City. The method used is a quantitative method with primary data taken using a questionnaire. This research used a sample of 172 respondents who were selected using the lemmeshow formula and purposive sampling technique. The population of this research is the community of OVO E-Wallet users in Malang City. The data was processed using multiple linear regression analysis methods. The research results show that perceived convenience (X1) has a positive and significant effect on interest in using (Y), perception of usefulness (X2) has a positive and significant effect on interest in using (Y), income (X3) has a positive and significant effect on interest in using (Y) , Age (X4) has a positive and significant effect on interest in using (Y) and education level (X5) has a negative and significant effect on interest in using (Y).